Primary sternal tuberculosis: A case report and literature review - Keerati Hongsakul (2018)
© 2015, SEAMEO TROPMED Network. All rights reserved. Mycobacterium tuberculosis can infect multiple organs and may rarely cause osteomyelitis of the sternum. We report a patient with primary sternal tuberculosis who presented with a chest wall mass. A core needle biopsy confirmed the diagnosis of tuberculosis. We review the literature regarding tuberculous osteomyelitis of the sternum.